2010
DOI: 10.4161/cc.9.20.13453
|View full text |Cite
|
Sign up to set email alerts
|

Non-redundant role for the transcription factor Gli1 at multiple stages of thymocyte development

Abstract: The Hedgehog (Hh) signaling pathway influences multiple stages of murine T-cell development. Hh signaling mediates transcriptional changes by the activity of the Gli family of transcription factors, Gli1, Gli2 and Gli3. Both Gli2 and Gli3 are essential for mouse development and can be processed to function as transcriptional repressors or transcriptional activators, whereas Gli1, itself a transcriptional target of Hh pathway activation, can only function as a transcriptional activator and is not essential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 46 publications
4
35
1
Order By: Relevance
“…These data suggest that the transient requirement of Gli1 at a certain point of differentiation appears to depend on cell types, even in skeletogenesis. In line with our findings, several groups recently reported that Gli1 affected the proliferation and differentiation of hematopoietic stem cells and thymocytes in studies of Gli1 Ϫ/Ϫ mice (26,27). Our findings support the idea that different Gli factors function in different contexts (28), and detailed analyses of Gli1 may help further reveal such diverse functions of Gli factors in various developmental processes.…”
Section: Discussionsupporting
confidence: 92%
“…These data suggest that the transient requirement of Gli1 at a certain point of differentiation appears to depend on cell types, even in skeletogenesis. In line with our findings, several groups recently reported that Gli1 affected the proliferation and differentiation of hematopoietic stem cells and thymocytes in studies of Gli1 Ϫ/Ϫ mice (26,27). Our findings support the idea that different Gli factors function in different contexts (28), and detailed analyses of Gli1 may help further reveal such diverse functions of Gli factors in various developmental processes.…”
Section: Discussionsupporting
confidence: 92%
“…As our findings were in contrast to several other reports describing an influence of Hh signaling on the transition from the double-positive (DP) to the single-positive (SP) stage of thymocyte development [22], [23], [24], we decided to repeat the analyses with mice backcrossed to the C57BL/6 background. Although the overall thymic cellularity (Figure 1A) and the percentages of double-negative (DN) thymocytes (Figure 1B,C) were similar in both genotypes, we found that the relative number of DP thymocytes was increased in Ptch flox/flox CD4Cre +/− mutant mice while the percentages of CD4 and CD8 SP thymocytes were decreased (Figure 1C).…”
Section: Resultscontrasting
confidence: 72%
“…Data for the differentiation, proliferation, and survival of the earliest DN thymocyte subsets, the transition from DN to DP, as a negative regulator of pre-TCR-induced thymocyte expansion (79)(80)(81)(82)(83), the transition from DP to SP, for TCR repertoire selection, at the CD4/ CD8 lineage decision (84,85), and negative selection (83) all support a role for Hh signaling in T cell development. In contrast, other work showed that the Hh signal transducer Gli1 is not needed to mediate the effects of Hh signaling at early stages of thymocyte differentiation (86), and gain-and loss-of-function genetic models of Smoothened show that it is not required for adult BM HSC self-renewal or differentiation or for thymocyte development (87). Although previous results for Ptc deletion in hematopoietic cells suggested a role in T cell development (82), subsequent experiments showed that it is dispensable for T cell development (88); the previously observed developmental block, resulting in a reduced number of ETPs (82), could be due to a defect in thymichoming progenitors (88).…”
Section: Hh-signaling Pathwaymentioning
confidence: 87%